Assertive Illocutionary Acts in Sherlock: The Abominable Bride Movie - Septhyana Suyono, Ni Putu Nana; Widiastuti, Ni Made Ayu (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl July, 2021)
This study is a pragmatic related and connected to illocutionary act in speech act. There are five types of illocutionary act based on Searle’s theory and they are assertive, directive, commissive, expressive and declarative. However, to make the analysis more specific, this study will be focused on assertive illocutionary act by using the theory proposed by Searle (1976). The types of assertive illocutionary act will be specifically described by explaining in what context of situation they are usually used in a conversation. The main reason why the researcher found this movie interesting to be the object of this study is because this movie has unique utterances which performed by its main characters, Sherlock Holmes and Dr. John Watson. We can also get more knowledge about the assertive illocutionary act which is the type that mostly happen during the movie. It is important to understand the utterance of the speaker in different context of situation and this movie shows a lot of ways the main characters utter with their intended meaning.